Influence of Terminal Bud Pinching On Growth and Yield of Chrysanthemum, Chrysanthemum Indicum L. (Journal of Bangladesh Academy of Sciences, 2012)
An experiment on pinching (viz. P0; without pinching and P1; with pinching) with 3 replications showed the tallest (37.7 cm) and the shortest plant (33.4 cm) without pinching and with pinching, respectively. Maximum number of leaves (30.1) and flowers (58.7) per plant were  recorded following pinching (P1); and minimum number of leaves (26.8) and flowers (37.9) per plant were from without pinching (P0). DOI: http://dx.doi.org/10.3329/jbas.v36i2.12971 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 251-255, 2012